2018
DOI: 10.1016/j.rboe.2018.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous treatment for waist and proximal pole scaphoid fractures

Abstract: ObjectiveAnalyze the percutaneous fixation technique for scaphoid fractures in the waist of the scaphoid and the proximal pole, and demonstrate its result.MethodsA retrospective cross-cohort study conducted from January 2005 to April 2015, aiming at the consolidation time, epidemiological profile, level of function, return to work, and complications.ResultsTwenty-eight patients were selected, with a mean of eight weeks of follow-up. They presented a mean age of 30.5 years, male prevalence (25 patients; 89.2%),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
(43 reference statements)
2
2
0
Order By: Relevance
“…Regarding epidemiology, the mean age of participants was 34.5±8.37. the majority of cases were male (67%) with right side prevalence (78%) and fall on outstretched hand was the major cause (67%), These results are similar to that reported by Severo et al (7) , who performed percutaneous treatment for 28 patients in which the mean age was 30.5 years, male prevalence was 89.2% with no prevalence of the dominant side and fall on the wrist was the main cause (78.5%).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Regarding epidemiology, the mean age of participants was 34.5±8.37. the majority of cases were male (67%) with right side prevalence (78%) and fall on outstretched hand was the major cause (67%), These results are similar to that reported by Severo et al (7) , who performed percutaneous treatment for 28 patients in which the mean age was 30.5 years, male prevalence was 89.2% with no prevalence of the dominant side and fall on the wrist was the main cause (78.5%).…”
Section: Discussionsupporting
confidence: 88%
“…These results are in line with the studies by Severo et al (7) who reported 92.80% excellent outcome, good (0%), fair (0%), and (7.20%) Poor result.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…All of the cases were recent fractures lasting less than three weeks. Severo et al [14], on the other hand, performed percutaneous treatment for 28 patients with a mean age of 30.5 years, a male prevalence of 89.2%, no prevalence of the dominant side, and a wrist fall as the primary aetiology (78.5%). Only patients with solitary scaphoid fractures and a longer period to presentation (4.16 weeks) were considered (range 1-8 weeks).…”
Section: Discussionmentioning
confidence: 99%